2017
DOI: 10.1039/c7ay00448f
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantitative analysis of three components in mixture samples based on NIR spectra with temperature effect

Abstract: The temperature effect is usually regarded as one of the interference parameters in the routine analysis of near infrared (NIR) spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…[6][7][8] Several studies have demonstrated that temperature changes affect the vibrational intensity of the molecular bonds in the near infrared (NIR) region, so the spectrum will change according to the temperature variation. [6][7][8][9][10][11] Bands in the NIR region can be an overlay of many bands that belong to different cluster sizes of molecules formed by the hydrogen bonding, shifted towards lower energies (longer wavelengths) as the degree of hydrogen bonding decreases because of the increase in temperature. [6][7][8][9][10][11] Increasing temperature dilates solvents and so to measure concentration accurately requires a correction factor for the coefficient of thermal expansion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Several studies have demonstrated that temperature changes affect the vibrational intensity of the molecular bonds in the near infrared (NIR) region, so the spectrum will change according to the temperature variation. [6][7][8][9][10][11] Bands in the NIR region can be an overlay of many bands that belong to different cluster sizes of molecules formed by the hydrogen bonding, shifted towards lower energies (longer wavelengths) as the degree of hydrogen bonding decreases because of the increase in temperature. [6][7][8][9][10][11] Increasing temperature dilates solvents and so to measure concentration accurately requires a correction factor for the coefficient of thermal expansion.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Bands in the NIR region can be an overlay of many bands that belong to different cluster sizes of molecules formed by the hydrogen bonding, shifted towards lower energies (longer wavelengths) as the degree of hydrogen bonding decreases because of the increase in temperature. [6][7][8][9][10][11] Increasing temperature dilates solvents and so to measure concentration accurately requires a correction factor for the coefficient of thermal expansion. However, volume expansion may impact absorbance less than the effect of temperature on the hydration of the chromophore compounds.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the multi-compounds in table wines were successfully quantified on the basis of 1 H NMR SC-3D spectra that were established by the repetition of the original corresponding 1 H NMR spectrum [14]; the amino acids in the yellow foxtail millet substrate were determined on the basis of the terahertz time-domain spectroscopy (THz-TDS) images that include the spectra of three different parameters [15]; three components in mixture samples were quantitatively analyzed on the basis of near-infrared (NIR) 3D spectra with temperature [16]. Here, we focus our attention on the later one.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in previous references, in the process of application of Tchebichef moments, the self-constructed ways were proposed to form self-constructed 3D spectra from conventional 2D spectra to extract the feature information for further analysis purpose. For example, the multi-compounds in table wines were successfully quantified on the basis of 1 H NMR SC-3D spectra that were established by the repetition of the original corresponding 1 H NMR spectrum [14]; the amino acids in the yellow foxtail millet substrate were determined on the basis of the terahertz time-domain spectroscopy (THz-TDS) images that include the spectra of three different parameters [15]; three components in mixture samples were quantitatively analyzed on the basis of near-infrared (NIR) 3D spectra with temperature [16]. Moreover, the other ways for data arrangement have also been reported, such as multivariate curve resolution-alternating least squares (MCR-ALS) method can be easily extended to the simultaneous analysis of multiple data sets through column-wise or row-wise augmented data matrices [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TM has few redundant information and no numerical approximation during the calculation. Therefore, TM methods have been more used recently …”
Section: Introductionmentioning
confidence: 99%